MANAGEMENT OF RESOURCE FLOWS AND RESILIENCE OF ENTERPRISES IN THE WELFARE ECONOMY (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In a changing environment, business entities are paying more and more attention to managing resource flows and resilience. The BANI-world has emerged as a response to pandemics, military actions and other processes that are changing in society. Business management creates the preconditions for the development of society, economy and welfare. Business plays a key role in shaping economic welfare. In such conditions, companies strive to maintain sustainability and competitiveness by effectively managing resource flows. It is resource flows that are the main factor in ensuring the company's resilienceThe purpose of the article. The aim of the study is to develop tools for managing enterprise resource flows and enterprise resilience. Despite a sufficient amount of scientific developments in the field of management of resource flows and enterprise resilience, the issue of developing an approach to their implementation remains unresolvedMethods. In order to achieve the goal and solve the tasks set, the paper uses comparative analysis to study the tools of adaptation management and adaptive marketing, to generalize and systematize the components of the R4S and R4E models, to establish the difference between the VUCA and BANI concepts, analysis and synthesis, to build an adaptive marketing strategy, architecture of adaptive management of resource flows and resilience of enterprises and to draw conclusions, the abstract and logical method.Results. The result of the study was the development of a scheme for managing resource flows and enterprise resilience using adaptive marketing and adaptive management tools. A model of enterprise resilience (R4E) has been developed, which includes 6 elements, including: diagnostics of BANI conditions of enterprise functioning, determination of the critical state of the enterprise, creation of a model of the current state of the enterprise, development of risk scenarios and analysis of vulnerabilities, formation of a new configuration of resilience (DFRs), monitoring of the model.Conclusions. The study found that resource flow management affects the resilience of enterprises in the BANI world. The concept of BANI indicates the chaotic and unpredictable nature of society, which has arisen as a result of pandemics and military operations. Enterprises operate in these conditions and form effective resource flow and resilience management schemes.
Keywords: socio-economic resilience, information flows, resource flows, reintegration of veterans into society, enterprise management, welfare economy.